“Claim vs. Reality”—A German Case Study on Modes and Functions of Sports-Pedagogical Communication - Jaitner, David; Koerner, Swen; Serwe-Pandrick, Esther (Frontiers in Sports and Active Living, 2021)
Academic sports pedagogy continuously assures itself of its disciplinary foundations and determines its position in the structure of modern sciences. While communication is based on differences, the distinction between claim and reality plays a crucial role in sports pedagogy. However, the forms and functions in which the distinction appears have not been more closely investigated in sports pedagogic. This article starts with this in mind, exemplarily focusing on academic sports pedagogy in Germany. While analyzing 212 scientific texts of sports-pedagogical provenance, three central variations of the distinction could be identified, which persist until today and are present in the discipline’s central discussion lines: (1) hierarchical demarcation, (2) unsystematic approach, (3) direct synthesis. From a functional point of view, the distinction between claim and reality continuously (re)organizes the relationship of sports pedagogy to other scientific disciplines, educational policy guidelines, and school practice expectations, thus proving to be a supporting pillar of disciplinary identity work.